The Relationship between Well-Being and Hypersensitivity among Young Adults - Maracineanu, I.G.; Truța, C. (Universitatea Transilvania Brasov, 2025)
The study investigates the relationship between personality traits, childhood environment, and well-being in young adults with increased sensitivity to sensory processing (118 participants, 20-35 years). The results show that there is no significant association between well-being and hypersensitivity, but these individuals present maladaptive traits, such as anxiety and depression. Emotional regulation and hypersensitivity are predictors of well-being, and individuals from adverse environments are at increased risk for behavioral disorders and psychopathology. Women have higher levels of hypersensitivity and emotional suppression, without significant differences in well-being or childhood experiences.
Keywords: well-being; hypersensitivity; childhood experiences; emotional regulation